Au-Ni nanoparticles: Phase diagram prediction, synthesis, characterization, and thermal stability. (September 2017) - Sopoušek, J.; Kryštofová, A.; Premović, M.; Zobač, O.; Polsterová, S.; Brož, P.; Buršík, J.
Abstract: The Au-Ni nanoparticles (NPs) were prepared by oleylamine solvothermal synthesis from metal precursors. The Au-Ni phase diagram prediction respecting the particle size was calculated by the CALPHAD method. The hydrodynamic size of the AuNi NPs in a nonpolar organic solvent was measured by the dynamic light scattering (DLS) method. The average hydrodynamic sizes of the nanoparticle samples were between 18 and 25 nm. The metallic composition of the AuNi NP samples was obtained by inductively-coupled plasma atomic emission spectroscopy (ICP-OES). The metallic fraction inside AuNi NPs was varied Au-(30–70) wt%Ni. The steric alkylamine stabilization was observed. The individual AuNi NPs were investigated by transmission electron microscopy (TEM). The dry nanopowder was also studied. The structures of the aggregated samples were investigated by scanning electron microscopy (SEM). The AuNi NPs reveal randomly mixed face-centered cubic (FCC) crystal lattices. The phase transformations were studied under inert gas and air. The samples were studied by differential scanning calorimetry (DSC).